PEMETAAN DAN PENZONAAN FUNGSI LAHAN DI KECAMATAN DUNGINGI : IMPLIKASI BAGI TATA RUANG WILAYAH - Imran, Mohammad; Osborne Narande, John Andrew; Apriyanto; F. Darkay, Al Dimas (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2025)
Land is one of the main factors in the development of a region, Gorontalo City as the capital of Gorontalo province is developing rapidly due to the increase in population, economic, social and cultural activities. The development of Gorontalo City has an impact on the development of the need for land use functions. The objectives of this study are: (1) to map the land functions spread across Dungingi District, Gorontalo City and (2) to identify residential zones, goods and services, wetlands and plantations. The research method used is spatial analysis through the application of Geographic Information Systems (GIS) to map the distribution of existing land functions and using the overlay method. The results of this study produce a visualization of the distribution of land functions and recommendations for sustainable regional spatial planning. The results of the study are expected to be a reference for local governments in managing effective land use.